2003
DOI: 10.1016/s1534-5807(03)00321-6
|View full text |Cite
|
Sign up to set email alerts
|

The E3 Ubiquitin Ligase AIP4 Mediates Ubiquitination and Sorting of the G Protein-Coupled Receptor CXCR4

Abstract: Ubiquitination of the chemokine receptor CXCR4 serves as a targeting signal for lysosomal degradation, but the mechanisms mediating ubiquitination and lysosomal sorting remain poorly understood. Here we report that the Nedd4-like E3 ubiquitin ligase AIP4 mediates ubiquitination of CXCR4 at the plasma membrane, and of the ubiquitin binding protein Hrs on endosomes. CXCR4 activation promotes CXCR4 colocalization with AIP4 and Hrs within the same region of endosomes. Endosomal sorting of CXCR4 is dependent on Hrs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
457
1
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(493 citation statements)
references
References 43 publications
30
457
1
5
Order By: Relevance
“…A rigorous study from the Raz group demonstrated in vivo that in zebrafish CXCR4 internalization is dispensable for cell motility and directional chemokine sensing, but essential for fine-tuning of migration allowing precise arrival of primordial germ cells [26]. Finally, CXCR4 internalization and its subsequent lysosomal degradation have also been reported [27], a mechanism that is implicated in rendering cells insensitive to chemokines and hence immobile.…”
Section: Keeping Chemotactic Receptors In Placementioning
confidence: 99%
“…A rigorous study from the Raz group demonstrated in vivo that in zebrafish CXCR4 internalization is dispensable for cell motility and directional chemokine sensing, but essential for fine-tuning of migration allowing precise arrival of primordial germ cells [26]. Finally, CXCR4 internalization and its subsequent lysosomal degradation have also been reported [27], a mechanism that is implicated in rendering cells insensitive to chemokines and hence immobile.…”
Section: Keeping Chemotactic Receptors In Placementioning
confidence: 99%
“…Residues-Chemokine receptors and other 7TMRs can be targeted to lysosomes by ubiquitination of lysine residues (15)(16)(17). There are two intracellular lysines in D6-Ala6 and D6-340 that are conserved across mammalian D6 sequences.…”
Section: The Reduced Stability Of D6-ala6 Is Dependent On Intracellulmentioning
confidence: 99%
“…D6 trafficking differs from signaling-competent chemokine receptors (and most other 7TMRs) that typically reside at the cell surface and become rapidly internalized only after activation by ligand. Extensive depletion of extracellular chemokines is limited by receptor desensitization and by receptor down-regulation which, in the case of CXC chemokine receptor 4 and other 7TMRs, is driven by monoubiquitination of intracellular lysines and subsequent passage to lysosomes for degradation (15)(16)(17).…”
mentioning
confidence: 99%
“…Hrs is ubiquitinated itself, and must be deubiquitinated for receptor sorting to the degradative pathway. This ubiquitination status is proposed to be regulated by Vps4 (Marchese et al, 2003b).…”
Section: Endosomal Sorting Of Ubiquitinated Cargomentioning
confidence: 99%